Shared vision between fathers and daughters in family businesses: the determining factor that transforms daughters into successors - Overbeke, Kathy K.; Bilimoria, Diana; Somers, Toni (Frontiers in Psychology, 2015)
Family businesses are critical to the United States economy, employing 63% of the workforce and generating 57% of GDP (University of Vermont, 2014). Family business continuity, however, remains elusive as approximately 70% of family businesses do not survive the second generation (Poza, 2013). In order to augment our understanding of how next generation leaders are chosen in family businesses, we examine daughter succession. Using a sample of pairs of family business fathers and daughters and drawing on an earlier study of the dearth of successor daughters in family businesses (Overbeke, Bilimoria, & Perelli, 2013), we reveal that shared vision between fathers and daughters is central to daughter succession. Self-efficacy and gender norms influence shared vision and when fathers and daughters share a vision for the future of the company, daughters are likely to be transformed into successors.